Analysis of strategy and implementation of head injury prevention programs: A case study of boxers at HAN Academy Malang - Padantya Devin Sugito (Sport, Exercise, and Injury, 2025)
Background: Boxing is a high-risk combat sport with a high probability of head injuries, so effective prevention strategies are essential for athlete safety. However, empirical evidence on the implementation of head injury prevention programs at the training academy level is still limited. Objectives: This study aims to explore strategies and the practical implementation of head injury prevention at the HAN Boxing Academy, Malang. Methods: A qualitative case study design was used with purposive sampling. Four participants (one coach and three active athletes) were recruited. Data were collected through document review, direct observation, and semi-structured interviews, which consisted of 15 guiding questions. Data were analyzed using a thematic analysis approach, which involved data reduction, data presentation, and conclusion. Methodological triangulation was applied to enhance credibility. Results: Three main themes emerged: (1) systematic emphasis on basic defensive techniques to minimize head collisions, (2) mandatory and consistent use of head protection during training sessions, and (3) active supervision by coaches combined with a gradual rehabilitation protocol, including competition restrictions for up to six months after a serious head injury. Participants considered head protection effective in reducing the severity of impacts, although the residual risk of head injury was still acknowledged. Conclusions: Head injury prevention in academies is implemented through an integrated approach that combines technical skill development, the use of protective equipment, and continuous monitoring. To strengthen its effectiveness, it is recommended that structured injury prevention protocols be implemented and closer collaboration with medical professionals be fostered.